Waist circumference, among metabolic syndrome components, predicts degraded trabecular bone score: a retrospective study of a female population from the 2005-2008 NHANES cohorts - Totaro, Maria; Barchetta, Ilaria; Sentinelli, Federica; Cimini, Flavia Agata; Palazzi, Sara; D’Alessandro, Francesco; Spagnolo, Luca; Dule, Sara; Barbonetti, Arcangelo; Cavallo, Maria Gisella; Baroni, Marco Giorgio (Frontiers in Endocrinology, 2024)
Background: Osteoporosis and metabolic syndrome (MetS) are conditions associated with ageing and chronic inflammation; among MetS’ components, visceral obesity has been correlated to low bone mineral density in postmenopausal women. However, data on an increased fracture risk in MetS are still contrasting. The trabecular bone score (TBS) is an indicator of bone quality and a potential predictive factor for fractures. We aim to explore the relationship between MetS components and TBS. Methods: we analyzed data from 3962 women in the 2005-2006 and 2007-2008 NHANES cohorts, for whom a valid TBS value was available. All analyses were adjusted for for the principal risk factors of altered bone metabolism. Results: An inverse significant association was observed between TBS and most of the MetS variables investigated, with the strongest correlation found with waist circumference (WC) (P <0.001). WC represented the major predictor of degraded TBS (P <0.001), in adjusted models considering age, 25(OH)Vitamin D, smoke and insulin resistance. Increased WC was significantly associated with the presence of bone fractures at the logistic regression analysis (P = 0.001) in all study participants and in the subgroup of women ≤50 years old after adjustment for potential confounders (P = 0.006). Conclusion: This study, using a large sample of women, found a negative association of MetS on bone health, mainly driven by visceral obesity.